2020
DOI: 10.1016/j.fertnstert.2020.08.233
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Detection of Blastocyst Ploidy (Euploid vs. Aneuploid) Using Artificial Intelligence (Ai) With Deep Learning Methods

Abstract: OBJECTIVE: The current method of preimplantation genetic testing for aneuploidy (PGT-A) involves invasive trophectoderm (TE) biopsy. Although PGT-A has improved the success rate per embryo transfer, it has notable limitations. These include the cost of sequencing, mosaicism, the skill required to biopsy TE cells, and the fact that only a select number of blastocysts (BLs) can be tested. Embryologists rely on morphological assessment and clinical information to select BLs for PGT-A. The development of noninvasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…3d). In addition, our DMS achieved higher accuracy than comparable published models on blastocysts (Barnes, et al, 2020, Huang, et al, 2021, Miyagi, et al, 2019, Ortiz, et al, 2021). Other published studies have indicated that clinometric data can further strengthen prediction which should be incorporated into future clinical applications (Barnes, Malmsten, Zhan, Hajirasouliha, Elemento, Sierra, Zaninovic and Rosenwaks, 2020, Ortiz, Morales, Lledo, Garcia-Hernandez, Cascales, Vicente, González, Ten, Bernabeu and Llácer, 2021).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…3d). In addition, our DMS achieved higher accuracy than comparable published models on blastocysts (Barnes, et al, 2020, Huang, et al, 2021, Miyagi, et al, 2019, Ortiz, et al, 2021). Other published studies have indicated that clinometric data can further strengthen prediction which should be incorporated into future clinical applications (Barnes, Malmsten, Zhan, Hajirasouliha, Elemento, Sierra, Zaninovic and Rosenwaks, 2020, Ortiz, Morales, Lledo, Garcia-Hernandez, Cascales, Vicente, González, Ten, Bernabeu and Llácer, 2021).…”
Section: Discussionmentioning
confidence: 60%
“…In addition, our DMS achieved higher accuracy than comparable published models on blastocysts (Barnes, et al, 2020, Huang, et al, 2021, Miyagi, et al, 2019, Ortiz, et al, 2021). Other published studies have indicated that clinometric data can further strengthen prediction which should be incorporated into future clinical applications (Barnes, Malmsten, Zhan, Hajirasouliha, Elemento, Sierra, Zaninovic and Rosenwaks, 2020, Ortiz, Morales, Lledo, Garcia-Hernandez, Cascales, Vicente, González, Ten, Bernabeu and Llácer, 2021). We recently demonstrated that hyperspectral imaging of cell autofluorescence was able to detect aneuploidy in in vitro cultured mouse blastocysts (Tan, Mahbub, Campbell, Habibalahi, Campugan, Rose, Chow, Mustafa, Goldys and Dunning, 2022).…”
Section: Discussionmentioning
confidence: 60%
“…We can anticipate that other similar full-paper publications will follow shortly, presenting new approaches aimed at embryo selection based on ploidy. These studies will perhaps target timelapse sequences (Barnes et al, 2020) and incorporate omics (Bori et al, 2021), patient and cycle characteristics (Jiang et al, 2021), noninvasive chromosome screening tests (Chavez-Badiola et al, 2020c), as well as new AI approaches. Building high-quality datasets from diverse settingswhile managing hype (VerMilyea et al, 2019) and expectations-are challenges that will remain.…”
Section: Ai For Non-invasive Ploidy Screeningmentioning
confidence: 99%
“…Chavez-Badiola et al ( 2020) developed a ranking system for ploidy status using this technology, with an impressive AUC of 0.70. Interestingly, two groups have investigated if there was an additive effect of using morphokinetic algorithms with artificial intelligence to improve diagnostic accuracy (Barnes et al 2020;Huang et al 2021). Barnes et al (2020) demonstrated that both work synergistically to improve the AUC from 0.62 when solely image analysis is used to 0.76 (Barnes et al 2020).…”
Section: )mentioning
confidence: 99%